2016
DOI: 10.9719/eeg.2016.49.2.105
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater-Stream Water Interaction Induced by Water Curtain Cultivation Activity in Sangdae-ri Area of Cheongju, Korea

Abstract: Most of riverside in Korea, in case of application of water curtain cultivation (WCC) technique, has been inveterately suffering from the gradual drawdown of groundwater level and related shortage of water resources during the WCC peak time. We believe that the water resources issue in these riverside areas can be effectively solved when the interaction between groundwater and nearby surface water is well understood. To investigate the connection between stream and ground water, and the influence of stream wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…For example, the groundwater can be degraded due to contaminated river water, while saline groundwater can be diluted by induced river water [17,18]. The decrease in groundwater temperature could also led to crop cold damage in water-curtain greenhouses [19]. Therefore, evaluating the impacts of weir operation on the groundwater system is required, while groundwater modeling can be used to predict the response of the aquifer system to the variations in the river level [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the groundwater can be degraded due to contaminated river water, while saline groundwater can be diluted by induced river water [17,18]. The decrease in groundwater temperature could also led to crop cold damage in water-curtain greenhouses [19]. Therefore, evaluating the impacts of weir operation on the groundwater system is required, while groundwater modeling can be used to predict the response of the aquifer system to the variations in the river level [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the stream‐aquifer interaction could affect groundwater temperature and quality, which could adversely affect greenhouse heating as well as crop irrigation. The groundwater temperature could decrease due to the intrusion of cold stream water during the pumping season (Moon et al ). The groundwater quality could be deteriorated by the polluted stream water (Ray et al ), while saline groundwater could be diluted by induced recharge (Lee et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Induced groundwater recharge by seasonal pumping in winter appears to have a large impact on the groundwater temperature near the corresponding stream (Kim et al ). A recent study in an area of water‐curtain cultivation showed temporal variations of groundwater temperature and a strong influence of stream water on the stable isotopic composition of groundwater (Moon et al ). The chemical characteristics of groundwater can also be changed by induced recharge (Hiscock and Grischek ; Ray et al ).…”
Section: Introductionmentioning
confidence: 99%